Lift up your hearts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Institutions and the African Farmer. Issues in Agriculture 14. C Eicher. CGIAR. 60 pp. 1999. Free of charge. CGIAR 1818 H St NW, Washington, DC 20433, USA. Fax: +1 202 473 8110 Email cgiar@cgiar.org